Chemical Composition, Fatty Acids, Total Phenolics and Antioxidant Activity of the Desert Truffle Terfezia Boudieri Chatin in the Northern Region of Saudi Arabia - Guetat, Arbi; Alzahrani, A. Khuzaim; Oueslati, Mohamed Habib; Elhaj, Abd Ealrhman M.; Bouajila, Jalloul; Shahhat, Ismail M. A. (Engineering, Technology & Applied Science Research, 2024)
Terfezia boudieri Chatin (T. boudieri), which belongs to the Terfeziaceae family, is a desert truffle growing naturally from mycorrhizal relationships with plants that inhabit the slightly moist sandy soils of some desert or semi-desert regions. The chemical examination of the methanolic extract of T. boudieri led to the isolation of a new ketone and the known compound mannitol. The structures of the 2 isolated compounds were resolved using spectroscopic analysis including 1D and 2D Nuclear Magnetic Resonance (NMR), Infrared (IR) spectroscopy and were supported by literature data. The GC-MS analysis of the Fatty Acids (FAs) of T. boudieri oils showed high Unsaturated FA (UFA) profile (78.72%). The major FAs were linoleic acid (62.36%) and oleic acid (14.7%). Comparing the extracts obtained, the methanolic extract revealed the highest levels of Total Phenolic Content (TPC) of 185.56 mg GAE/100 g of truffle, thus the same extract showed the best results for antioxidant activity.